2004
DOI: 10.1161/01.cir.0000136025.96811.76
|View full text |Cite
|
Sign up to set email alerts
|

AMP-Activated Protein Kinase Inhibits Angiotensin II–Stimulated Vascular Smooth Muscle Cell Proliferation

Abstract: Background-AMP-activated protein kinase (AMPK) is a stress-activated protein kinase that works as a metabolic sensor of cellular ATP levels. Here, we investigated whether AMPK signaling has a role in the regulation of the angiotensin II (Ang II)-induced proliferation signal in rat vascular smooth muscle cells (VSMCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
149
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(169 citation statements)
references
References 42 publications
18
149
2
Order By: Relevance
“…Recently, it has been discovered that AMPK inhibits Ang II-stimulated vascular smooth muscle cell proliferation. 20 Several reports indicate that the antidiabetic adipocytokine adiponectin, which activates AMPK, has antiatherosclerotic effects. [21][22][23] Moreover, adiponectin activates AMPK and inhibits agonist-stimulated myocardial hypertrophy and ERK activation, as well as ERK transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been discovered that AMPK inhibits Ang II-stimulated vascular smooth muscle cell proliferation. 20 Several reports indicate that the antidiabetic adipocytokine adiponectin, which activates AMPK, has antiatherosclerotic effects. [21][22][23] Moreover, adiponectin activates AMPK and inhibits agonist-stimulated myocardial hypertrophy and ERK activation, as well as ERK transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, AMPK activation not only inhibits cancer cell growth but also non-cancer cells, such as vascular smooth muscle cells, endothelial cells, etc (Zhang et al, 2008;Song et al, 2011). Subcutaneous injection of AICAR, which is an AMPK activator, for 2 weeks suppresses neointimal formation after transluminal mechanical injury of the rat femoral artery (Nagata et al, 2004). In deed, resveratrol has been reported to stimulate AMPK in kidney collecting duct cells and neurons (Dasgupta et al, 2007;Weixel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…AMP-activated protein kinase (AMPK) regulates the involved cellular processes in cellular energy status (Hardie and Carling 1997). Recently, scientifi c evidences have shown that AMPK activation may inhibit the cell proliferation and induce cell apoptosis in cancer cells (Nagata et al 2004). It has been suggested that curcumin-induced cell death in CaOV3 ovarian cancer cells through activating p38-dependent AMPK is reversible by AMPK and p38 inhibitors (Pan et al 2008).…”
Section: Th E Eff Ect Of C Longa and Curcumin On The Female Reproducmentioning
confidence: 99%